2018
DOI: 10.1016/j.jaapos.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Ocular complications in a young pediatric population following bone marrow transplantation

Abstract: Due to the high incidence of cataract formation in this population, especially those enduring a treatment regimen with total body irradiation, we propose screening examinations by a pediatric or general ophthalmologist at least annually. We also urge a low threshold for treatment of dry eye syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…This may be due to our small sample size. Unlike other authors, 28 our study showed an association between oGVHD and cataracts. The potentially significant visual impact of cataracts highlights the importance of ophthalmological assessments in this population.…”
Section: Rationale For Ogvhd Associationscontrasting
confidence: 90%
See 1 more Smart Citation
“…This may be due to our small sample size. Unlike other authors, 28 our study showed an association between oGVHD and cataracts. The potentially significant visual impact of cataracts highlights the importance of ophthalmological assessments in this population.…”
Section: Rationale For Ogvhd Associationscontrasting
confidence: 90%
“…In addition, the increased prevalence of ocular complications related or unrelated to oGVHD after transplants has led other authors to advocate for yearly examinations. 19,28 Based on our findings, we advocate for frequent follow-ups, especially in patients with cutaneous, pulmonary, or multiorgan involvement of GVHD.…”
Section: Discussionmentioning
confidence: 79%
“…Suh et al 16 reported that ocular changes developed in 51% of pediatric patients after HSCT and the frequency of dry eye syndrome was 12.5% at a mean age of 8.4 years. Hoehn et al 17 found the prevalence of dry eye syndrome in 14-year-olds as 41.4%. In our series, dry eye was detected in 30 (63.8%) of 47 patients with GVHD at a mean age of 11.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found a 10-year cumulative incidence of cataracts of 15% (95% CI, 11%-19%) for patients exposed to TBI, whereas other studies in children and adults have reported rates of 30% to 70% for cataract development at 10 years after transplant for patients exposed to fractionated TBI. [40][41][42] However, it is possible that technological advances in radiotherapy techniques beginning in the year 2000 may have contributed to less ocular toxicity in recent years. Similarly, as mentioned earlier, the low rate of gonadal dysfunction reported in this cohort was quite low.…”
Section: Discussionmentioning
confidence: 99%